Persepsi Terhadap Iklan Junk Food Pada Siswa SMA 1 Karangdowo Klaten - Setyawan, Gandhi, Pamudya Kurnia, STP., M.Agr, Muwakhidah, SKM., M.Kes (2015)
Background: One of factors affecting teenagers to consume junk food the effectiveness of elektronik media advertising. Purpose: The purpose of this study was to determine perceptions about McDonald's junk food advertisement in high school 1 of Karangdowo students. Method: The method used in this study was descriptive with the design of the correlation study. Population this research were 65 students grade X of SMA Negeri 1 Karangdowo, while subjects were 45 students of class X A, B and C SMA Negeri 1 Karangdowo. Results: The results showed that the students had a keen perception about junk food after watching junk food advertisement (60.00%). Students were interested in the advertisement because of its appearance of and storyline that correspond with the age of the students. Conclusion: After given advertisement, high school students 1 Karangdowo interestedin advertising junk food. The interest of students influenced by the look andstory line